Ocular Tuberculosis in Human Immunodeficiency Virus and Systemic Tuberculosis Co-infected Patients. (4th July 2021) - Jain, Sahil; Bajgai, Priya; Kaur, Savleen; Dogra, Mohit; Sharma, Aman; Sharma, Kusum; Katoch, Deeksha; Dogra, Mangat R.; Gupta, Vishali; Singh, Ramandeep
ABSTRACT: Purpose : To describe the prevalence and clinical findings of ocular tuberculosis (TB) in Human immunodeficiency virus (HIV) and systemic TB co-infected patients. Methods : In this prospective, observational, non-comparative case series, we included HIV and systemic TB co-infected patients, who underwent a detailed ophthalmic and systemic evaluation. Results : Of 85 patients, ocular tuberculosis was seen in eleven patients and their 16 eyes (12.9%). Without the benefit of eye exam, the diagnosis of disseminated TB was missed in 5/52 (9.6%) and 2/25 (8%) of patients clinically assumed to have pulmonary and Extrapulmonary TB, respectively. Conclusion : HIV patients with the disseminated TB have higher risk for ocular TB. As ocular symptoms are rare, still all of them need a detailed ocular examination to look for active ocular TB which will reclassify isolated pulmonary/extrapulmonary to disseminated TB warranting a detailed systemic examination.